Association between personal and environmental factors with recent stress in nursing students (Research, Society and Development, 2020)
This study aimed to assess the association between personal and environmental factors with recent stress in nursing students. This is a cross-sectional study with a quantitative approach carried out with 209 nursing students. Data were collected using a Sociodemographic Questionnaire, Inventory of Symptoms of Stress (ISSL) for recent stress, Questionnaire on Trauma in Childhood (CTQ), Perceived Stress Scale (PSS-14) and Rosenberg's Self-Esteem Scale. Among the students, 163 (78%) had recent stress, the majority in the resistance phase 120 (57.4%) and with manifestations of psychological symptoms 121 (57.9%). Recent stress was associated with health problems, medication use, self-reported stress, perceived stress and demands for social readjustment. The identification of factors that predispose to recent stress is essential for planning interventions focused on protecting the health of nursing students.